Gold-Based Nanoplataform for the Treatment of Anaplastic Thyroid Carcinoma: A Step Forward - Amaral, Mariana (2021)
Anaplastic thyroid carcinoma (ATC) is a very rare subtype of thyroid carcinoma and one of the most lethal malignancies. Poor prognosis is mainly associated with its undifferentiated nature, inoperability, and failing to respond to the typically used therapies for thyroid cancer. Photothermal Therapy (PTT) entails using light to increase tissues’ temperature, leading to hyperthermia-mediated cell death. Tumours are more susceptible to heat as they are unable to dissipate it. By using functionalized gold nanoparticles (AuNPs) that transform light energy into heat, it is possible to target the heat to the tumour. This study aims to formulate ATC-targeted AuNPs able to convert near-infrared light into heat, for PTT of ATC. Different AuNPs were synthetized and coated. Size, morphology, and surface plasmon resonances band were determined. The optimized coated-AuNPs were then functionalized with ligands to assess ATC’s specificity. Safety, efficacy, and selectivity were assessed in vitro. The formulations were deemed safe when not irradiated (>70% cell viability) and selective for ATC. However, when irradiated, holo-transferrin-AuNPs were the most cytotoxic (22% of cell viability). The biodistribution and safety of this formulation was assessed in vivo. Overall, this novel formulation appears to be a highly promising approach to evaluate in a very near future.